Determinants of Risky Assets Investment: An Extended Information-Motivation-Behavioural Skills Model - Hii, Ivy Siaw Hung (Curtin University, 2020)
Stock market participation plays a crucial role in individuals’ financial well-being and also a country’s financial market development. This study aims to examine the determinants of individuals’ risky assets investment in Malaysia. By integrating the information-motivation-behavioural skills (IMB) model and theory of basic values, this study investigates the influence of information (financial literacy, advice-seeking) and motivation (attitude towards investing, personal values, social norm) on risky assets investment directly and indirectly through behavioural skills (financial self-efficacy).